Innovation in Processing Inorganic Waste into Ecobricks: An Environmentally Friendly Solution in Panciro Village, Bajeng District, Gowa Regency - Samputri, Salma; Maru, Rosmini; Nasrul, Nasrul; Aisyah, Nur; Nuryulianti, Nuryulianti; Riska, Riska; Zulkifli, Sofyan; M Nur, Medar; Arfandi, Arfandi (UNIVERSITAS NEGERI MAKASSAR, 2025)
Panciro Village faces significant problems related to the accumulation of plastic waste that is carelessly dumped in rivers, roadsides, and empty land. This study explores the application of the ecobrick method as an alternative solution to plastic waste. The purpose of this study was to determine the perception of the Panciro Village community regarding waste management with the ecobrick method, evaluate the effectiveness of ecobricks in reducing plastic waste and analyze the challenges and opportunities for implementing ecobricks as an environmentally friendly solution in Panciro Village. This research method uses a descriptive qualitative approach with data collection through observation, interviews and documentation. The results, the population density of Panciro Village contributed to the increase in waste volume. The positive perception of the community towards ecobricks as a better solution than burning or littering, the effectiveness of ecobricks is considered moderate to significant depending on the level of community participation. The main challenges in implementing ecobricks include the process of shredding waste and the lack of public awareness. Ecobricks have economic value if managed properly. This study recommends technological innovations and more efficient methods to facilitate the process of making ecobricks.